A critical assessment of the long-term changes in the wintertime surface Arctic Oscillation and Northern Hemisphere storminess in the ERA20C reanalysis. (24th August 2018) - Bloomfield, H C; Shaffrey, L C; Hodges, K I; Vidale, P L
Abstract: This study investigates the robustness of the long-term changes in the wintertime surface Arctic Oscillation (AO) in the ERA20C reanalysis. A statistically significant trend in the AO is found in ERA20C over the period 1900–2010. These long-term changes in the AO are not found in two other observational datasets. The long-term change in the AO in ERA20C is associated with statistically significant negative trend (approximately −6 hPa per century) in mean-sea level pressure (MSLP) over the Northern Hemisphere polar regions. This is not seen in the HADSLP2 observational dataset, suggesting that the trends in the ERA20C AO index may be spurious. The spurious long-term changes in MSLP and the AO index in ERA20C result in a strengthening of the meridional MSLP gradient in ERA20C. The strengthening of the meridional MSLP gradient is consistent with increases in wintertime storminess in Northern Europe and the NH high latitudes.